Changes aesthetic in animation: issues of artistic pattern, technological advancement or market? - Braga Junior, Amaro Xavier; Paiva, Ana Lorena Nascimento (Anagrama, 2020)
The aim of this article is to analyze the profile of the aesthetic changes in the cartoons exhibited in Brazil in the last decades, based on the questions related to the artistic patterns of production, the technological advances and the economic market in which the productions are involved. It takes as a theoretical basis the aesthetics of nonsense and the sequentiality to select and evaluate the role of the changes and their impacts on the constitution of the episodes, profile characterization of the characters and general theme of the drawings. Evaluates the influence of the ClassInd - the indicative classification in Brazil - in the aesthetics of the drawings. Methodologically, it is the analysis of a panorama of animations, selected intentionally, from a content analysis, focused on the innovations that they instituted in the market. It proposes, in essay form, new multifaceted criteria to understand the process of production of animations.